The Effect of Opportunity Recognition and Organisation Capability on SME Performance in Indonesia Moderated by Business Model Innovation - Hendry Hartono; Reeya Ardini (Bina Nusantara University, 2022)
The research aimed to analyze the effect of opportunity recognition and organisation capability on SME's performance which is moderated by Business Model Innovation. It also aimed to find out and analyse the variables that most significantly affect SME's performance in Jakarta. Data collection were done by collectting questionnaires with 100 respondents who had business. In analysing data, the research used associative methods and moderated regression analysis. The results indicate that opportunity recognition and organisation capability have a significant effect on SME performance, and Business Model Innovation as moderator reduces the influence of opportunity recognition on SME performance but increase the influence of organisation capability on SME performance. Opportunity recognition and organisation capability have a relationship with SME performance, as evidenced by moderated regression analysis (β) of 1,589 and 0,479. After the Business Model Innovation moderates the two variables, the opportunity recognition relationship to SME performance has decreased to 0,657, and organisational capability to SME performance has increased to 0,724. Opportunity recognition, organisation capability, and Business Model Innovation also have a simultaneous influence on SME performance.